2004
DOI: 10.1002/jcp.20215
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of fibrotic markers in repairing corneas of mice deficient in Smad3

Abstract: The cytokine transforming growth factor-beta (TGF-beta) is a key mediator of fibrosis in all organs. Expression of fibrotic markers in repairing cutaneous wounds is reduced in mice lacking Smad3, a downstream cytoplasmic mediator of TGF-beta signaling (Ashcroft et al., 1999, Nat Cell Biol 1(5):260-266). This is correlated with a reduction in inflammation, and thus in the blood elements thought to be a significant source of TGF-beta at the wound site, the principle form being TGF-beta1. Since the major cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…2A,B). Fibrotic markers, such as a-smooth muscle actin that marks myofibroblasts, begin to be expressed in the corneal stroma ,7 days after injury (Stramer et al, 2005) and we found their expression to be maximal by 3 weeks. Therefore we collected corneas 3 weeks following chemical injury and stained using Fig.…”
Section: Mmp12 Protects Against Corneal Stromal Myofibroblast Transfomentioning
confidence: 52%
“…2A,B). Fibrotic markers, such as a-smooth muscle actin that marks myofibroblasts, begin to be expressed in the corneal stroma ,7 days after injury (Stramer et al, 2005) and we found their expression to be maximal by 3 weeks. Therefore we collected corneas 3 weeks following chemical injury and stained using Fig.…”
Section: Mmp12 Protects Against Corneal Stromal Myofibroblast Transfomentioning
confidence: 52%
“…We used phalloidin staining to identify changes in filamentous actin stress fibers arrangement in ECs that is characteristic for active fibroblasts [19]. Upon TGF-β treatment, MS-1 cells reorganized their actin cytoskeleton to the long stress fibers that cross the cell body, as previously described [40].…”
Section: Discussionmentioning
confidence: 99%
“…Smads are one of the major downstream cytoplasmic mediators of TGF-β signaling in ECs [10-13]. The role of Smad3 in TGF-β-induced EndMT was also documented in different types of ECs, whereas the function of Smad2 in fibrosis induction in response to TGF-β is still not clear [10, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Fibrosis is only observed in corneal injuries that include rupture of the epithelial basement membrane and wounding of the stroma [116]. Similar to dermal repair in the skin, PDGF and TGF-β are pivotal mediators of the corneal fibrotic response [117]. Due to the angiogenic privilege, platelets as critical source of PDGF and TGF-β are virtually absent, although their accumulation around the limbal vessels after wounding has been reported [118].…”
Section: The Fibrotic Response In Corneal Repairmentioning
confidence: 99%